Niobium Peroxide‐Catalyzed Selective Epoxidation of Allylic Alcohols. Issue 11 (22nd September 2014) - Chen, Chen; Zhao, Xiuge; Chen, Jizhong; Hua, Li; Zhang, Ran; Guo, Li; Song, Baoning; Gan, Huimei; Hou, Zhenshan
Abstract Modified niobium peroxides were prepared and used for catalyzing the epoxidation of allylic alcohols with hydrogen peroxide in the absence of any other solvent under ice bath conditions. Niobium peroxides modified with ionic liquid‐type 1‐dodecyl‐3‐methylimidazolium hydroxide or conventional tetradecyl trimethyl ammonium hydroxide surfactants demonstrated excellent yields (80–99 %) for the epoxidation of allylic alcohols to their epoxides even if the reaction was performed without any other solvent at 0 °C for 0.5 h. The catalyst characterization demonstrated that the surfactant molecules were anchored on the surface of the niobium catalyst by weak noncovalent interactions. Compared with niobium peroxides, the modified amphiphilic catalysts allowed easier accessibility to hydrophobic substrates and thus demonstrated high reaction rate and excellent recyclability for the epoxidation under mild conditions.